HUBUNGAN PERCAYA DIRI TERHADAP PRESTASI BELAJAR SISWA SMK NEGERI 4 PANDEGLANG TAHUN AJARAN 2020/2021 - Cahya Supiyanti; Deasy Yunika Khairun; Bangun Yoga Wibowo (Jurnal Penelitian Bimbingan dan Konseling, 2023)
AbstractThis research is motivated by the lack of self-confidence of students caused by low learning achievement. This study aims to determine the effect of self-confidence on student achievement in class X Software Engineering Expertise Program at SMKN 4 Pandeglang. This study uses a quantitative approach. The population of this study was all students of class X Software Engineering Expertise Program at SMKN 4 Pandeglang as many as 104 students. The sample that the author uses is a saturated sampling technique. The tools used for data collection are observations, questionnaires and documentation. Test the validity of the instrument using the validity with a significant level of 5%. The reliability test of the confidence scale instrument was calculated using the Cronbach Alpha formula. Data analysis and hypothesis testing used descriptive analysis using a Likert scale, and a simple linear regression technique had a significance value of 5%. The results showed that self-confidence had a positive and significant effect on student achievement. This is indicated by a significance of 0.000 (p < 0.05) and the regression line equation Y = 34.118 + 0.484X, which means that if self-confidence is increased by 1%, learning achievement will increase by 0.484. The conclusion of this study is that self-confidence can positively affect student achievement. There is an effective contribution of the self-confidence variable to student achievement of 19.1% and the remaining 80.9% is influenced by other factors. Based on the results of research on class X students of the Software Engineering Expertise Program at SMKN 4 Pandeglang, the percentage of confidence and student achievement in the majority of students are in the fairly good category.Keywords: Confidence, Student Achievement